THE INFLUENCE OF BANKING SERVICE QUALITY ON BANK CUSTOMER SATISFACTION IN SURAKARTA CITY - Wardhana, Galih Wisnu (The journal of contemporary issues in business and government, 2020)
Customer satisfaction is an important aspect that needs to be considered in managing the banking services industry. The bank industry that is able to provide customer satisfaction will be able to compete with other similar industries. This study aims to analyze the effect of effectiveness and assurance, access, price, tangible, service portfolios, and reliability on Bank Rakyat Indonesia (BRI) Customer Satisfaction in Surakarta. This study involved 100 BRI customers as respondents. The selection of respondents uses incidental sampling techniques. This study reveal that effectiveness and assurance, process, price, tangible, and reliability have a positive effect on bank customer satisfaction. Meanwhile, the service portfolio shows that there is no influence on customer satisfaction. Also, simultaneously the variables of effectiveness and assurance, access, price, tangible, service portfolio, and reliability affect customer satisfaction in the BRI of Surakarta City. This study has implications for banking practitioners in improving the quality of bank services.